The Effectiveness of Letrozole-Electroacupuncture Adjuvant Therapy in Reducing Resistance and Pulsatility Indices in Women with Polycystic Ovarian Syndrome - Dhamayanti Eka Octavia; Uki Retno Budihastuti; Eriana Melinawati; Nutria Widya Purna Anggraini; Eric Edwin Yuliantara; Ida Nurwati; Cahyono Hadi (Journal of Maternal and Child Health, 2020)
Background: Polycystic Ovarian Syndrome (PC